OC-005 A Multicenter, Double-Blind, Placebo (PBO)-Controlled Ph3 Study of Ustekinumab (UST), A Human IL-12/23P40 MAB, in Moderate-Severe Crohn's Disease (CD) Refractory to anti-TNFΑ: UNITI-1. (17th August 2016) - Rutgeerts, P; Gasink, C; Blank, M; Lang, Y; Johanns, J; Gao, L-L; Sands, B; Hanauer, S; Feagan, B; Targan, S; Ghosh, S; de Villiers, W; et al.
Abstract : Introduction: In a Ph2b study(CERTIFI), 1 UST intravenous(IV) induction followed by subcutaneous(SC) maintenance was effective in moderate-severe CD refractory to anti-TNF therapy. This Ph3 study examined efficacy&safety of IV UST induction in these pts. Methods: Pts with moderate-severe CD(CDAI 220–450) who previously failed/were intolerant to ≥1 TNF-antagonist were randomised 1:1:1 at Wk0 to a single dose of IV PBO, UST 130 mg, or weight-based tiered UST dosing 6 mg/kg. Primary endpoint was clinical response at Wk6(baseline [BL] CDAI score reduced by ≥100); pts with BL CDAI ≥220 to ≤248 were considered in clinical response if CDAI score of <150 was present. At Wk8, pts transitioned to the IM-UNITI maintenance study or were followed to Wk20. Results: The 741 randomised pts had history of TNF-antagonist failure, with BL median CDAI = 317, CRP = 9.9 mg/L, and prior disease duration of 10.1 yrs. Of these, 51% had previously failed ≥2 anti-TNFs with 29.1%, 69.4%, and 36.4% of pts, respectively. Clinical response at Wk6 was observed in 33.7%/34.3% of the 6 mg/kg/130 mg UST grps vs 21.5% on PBO(p = 0.003, p = 0.002, respectively). Clinical remission(CDAI < 150) at Wk8 was seen in 20.9%/15.9% vs 7.3% on PBO(p < 0.001, p = 0.003, respectively). Clinical response at Wk8 was seen in 37.8%/33.5% vs 20.2% on PBO(each p ≤ 0.001). Proportion of pts with 70 pt CDAI response at Wk6 was 43.8%/46.1% vs 30.4% on PBO(p = 0.002, p < 0.001, respectively) and at first post-BL Wk3 visit, 40.6%/38.4% vs 27.1% on PBO(p = 0.001, p = 0.009, respectively). Both IV UST induction doses resulted in significant improvements in CDAI, IBDQ, CRP, faecal lactoferrin and calprotectin vs PBO. Rates of AEs, SAEs, and infections were similar in the UST&PBO grps. One opportunistic infection(listeria meningitis) was reported in the 6 mg/kg UST grp. No malignancies, deaths, major adverse cardiovascular events, or TB occurred in UST-treated pts through Wk20. Conclusion: In a population of moderate-severe CD pts refractory to ≥1 prior TNF-antagonists, IV UST induced clinical response and remission and was well-tolerated throughout induction, confirming the previous positive induction data from CERTIFI. Reference: 1 Sandborn WJ, et al . N Engl J Med 2012;367 :1519–1528. Disclosure of Interest: P. Rutgeerts Consultant for: J&J, Merck, UCB, AbbVie, Millenium/Takeda, Genentech/Hoffman LaRoche, Medimmune/AstraZeneca/Amgen, Merck/Serono, Bristol Myers Squibb, Robarts, Tillotts Pharma, Conflict with: Lectures for J&J, Merck, AbbVie, C. Gasink Shareholder of: Janssen, Employee of: Janssen, M. Blank Employee of: Janssen, Y. Lang Shareholder of: Janssen, Employee of: Janssen, J. Johanns Shareholder of: Janssen, Employee of: Janssen, L.-L. Gao Shareholder of: Janssen, Employee of: Janssen, B. Sands Grant/research support from: Janssen, Consultant for: Janssen, S. Hanauer Grant/research support from: Janssen, Consultant for: Janssen, Conflict with: Lecturer for Janssen, B. Feagan Grant/research support from: Abbott/AbbVie, Amgen, Astra Zeneca, Bristol-Myers Squibb (BMS), Janssen Biotech (Centocor), JnJ/Janssen, Roche/Genentech, Millennium, Pfizer, Receptos, Santarus, Sanofi, Tillotts, UCB Pharma, Consultant for: Abbott/AbbVie, Actogenix, Akros, Albireo Pharma, Amgen, Astra Zeneca, Avaxia Biologics Inc., Avir Pharma, Axcan, Baxter Healthcare Corp., Biogen Idec, Boehringer-Ingelheim, Bristol-Myers Squibb, Calypso Biotech, Celgene, Elan/Biogen, EnGene, Ferring Pharma, Roche/Genentech, GiCare Pharma, Gilead, Given Imaging Inc., GSK, Ironwood Pharma, Janssen Biotech (Centocor), JnJ/Janssen, Kyowa Kakko Kirin Co Ltd., Lexicon, Lilly, Lycera BioTech, Merck, Mesoblast Pharma, Millennium, Nektar, Nestles, Novonordisk, Pfizer, Prometheus Therapeutics and Diagnostics, Protagonist, Receptos, Salix Pharma, Serono, Shire, Sigmoid Pharma, Synergy Pharma Inc., Takeda, Teva Pharma, TiGenix, Tillotts, UCB Pharma, Vertex Pharma, VHsquared Ltd., Warner-Chilcott, Wyeth, Zealand, Zyngenia, Speaker bureau with: Abbott/AbbVie, JnJ/Janssen, Takeda, Warner-Chilcott, UCB Pharma, Conflict with: Patent holder; Member Scientific Advisory board, Abbott/AbbVie, Amgen, Astra Zeneca, Avaxia Biologics Inc., Bristol-Myers Squibb, Celgene, Centocor Inc., Elan/Biogen, Ferring, JnJ/Janssen, Merck, Nestles, Novartis, Novonordisk, Pfizer, Prometheus Laboratories, Protagonist, Salix Pharma, Takeda, Teva, TiGenix, Tillotts Pharma AG, UCB Pharma; Member, Board of Directors Officer – Robarts Clinical Trials Inc, S. Targan Grant/research support from: Cedars-Sinai Medical Centre, Consultant for: Janssen, NuMedii, Inc., Conflict with: Advisory board for the Seaver Foundation; Scientific Advisory Board Member Symbiotix, S. Ghosh Grant/research support from: Abbvie, Conflict with: International Steering Committees: Janssen, Abbvie, Pfizer, Receptos, BMS, Aerpio; Advisory Committees: Takeda, Abbvie, Janssen, Pfizer, Allergan, W. de Villiers Conflict with: member of steering committee, active participant as investigator, J.-F. Colombel Consultant for: Pfizer, Takeda, Protagonist Therapies, Celgene, Genentech, Second Genome, Vertex, Amgen, Merck Sharp Dohme, Janssen, Nestle, AbbVie, Tigenix, Receptos, Conflict with: Speaker for AbbVie, Ferring, Shire, Takeda, S. Lee Grant/research support from: AbbVie Pharmaceuticals UCB Pharma Janssen Pharmaceuticals, Inc. Salix Pharmaceuticals Takeda Pharmaceuticals, Inc. Celgene Pharmaceuticals, Inc. Amgen Pharmaceuticals, Inc. Pfizer Pharmaceuticals, Inc., Consultant for: UCB Pharma Robarts Mesoblast Cornerstones Janssen Pharmaceuticals, Inc. Takeda Pharmaceuticals, Inc., P. Desreumaux Grant/research support from: 1. Ferring, St Prex, Suisse 2. Ferring, Danemark 3. Giuliani SpA, Milano, Italy 4. Lesaffre, Marcq en Baroeul, France 5. Roquette, Lestrem, France 6. Sanofi-Synthelabo, Paris, France 7. UCB Pharma, Paris, France 8. Yoplait, Paris, France 9. Omega Pharma, Belgium, Consultant for: 1. Biofortis, Nantes, France 2. Ferring, St Prex, Suisse 3. Giuliani SpA, Milano, Italy 4. Roquette, Lestrem, France 5. UCB Pharma, Paris, France 6. Txcell, Nice, France 7. Lesaffre, Marcq en Baroeul, France 8. MSD, France 9. Abbott, France 10. Norgine, France 11. Genfit, France 12. OmegaPharma International 13. Ppm, Switzerland 14. Kitozyme, Belgium 15. LFB, France, Conflict with: Lecture fees: 1. Ferring, Paris, France 2. Ferring, London, UK 3. Shire Pharmaceuticals, USA 4. UCB Pharma, Paris, France 5. MSD, France 6. Norgine, France 7. Abbott, France 8. Pileje, France, E. Loftus Jr Grant/research support from: Takeda, UCB, Janssen, AbbVie, Genentech, Celgene, Amgen, Pfizer, Gilead, Receptos, Robarts Clinical Trials, Consultant for: Takeda, UCB, Janssen, AbbVie, Genentech, Celgene, Theradiag, Seres Therapeutics, Sun Pharmaceuticals, Bristol-Myers Squibb, S. Vermeire Grant/research support from: Abbvie, MSD, Takeda, Consultant for: Abbvie, MSD, Takeda, Ferring, Genentech/Roche, Shire, Pfizer, Galapagos, Mundipharma, Hospira, Celgene, Second Genome, Janssen, Conflict with: Lectures: Abbie, MSD, Takeda, Ferring, Falk Pharma, Hospira, Tillotts, W. Sandborn Grant/research support from: Receptos, Exact Sciences, Amgen, the American College of Gastroenterology, Broad Foundation, Prometheus Laboratories, AbbVie, Boehringer Ingelheim, Takeda, Atlantic Pharmaceuticals, Janssen, Bristol-Myers Squibb, Genentech, Pfizer, and Nutrition Science Partners, Conflict with: Personal fees from Receptos, Prometheus Laboratories, AbbVie, Boehringer Ingelheim, Takeda, Atlantic Pharmaceuticals, Janssen, Bristol-Myers Squibb, Genentech, Pfizer, Nutrition Science Partners, Kyowa Hakko Kirin, Millennium Pharmaceuticals, Celgene Cellular Therapeutics, Santarus, Salix Pharmaceuticals, Catabasis Pharmaceuticals, Vertex Pharmaceuticals, Warner Chilcott, Gilead Sciences, Cosmo Pharmaceuticals, Ferring Pharmaceuticals, Sigmoid Biotechnologies, Tillotts Pharma, Am Pharma BV, Dr. August Wolff, Avaxia Biologics, Zyngenia, Ironwood Pharmaceuticals, Index Pharmaceuticals, Nestle, Lexicon Pharmaceuticals, UCB Pharma, Orexigen, Luitpold Pharmaceuticals, Baxter Healthcare, Ferring Research Institute, Amgen, Novo Nordisk, Mesoblast Inc., Shire, Ardelyx Inc., Actavis, Seattle Genetics, MedImmune (AstraZeneca), Actogenix NV, Lipid Therapeutics Gmbh, Eisai, Qu Biologics, Toray Industries Inc., Teva Pharmaceuticals, Eli Lilly, Chiasma, TiGenix, Adherion Therapeutics, Immune Pharmaceuticals, Celgene, Arena Pharmaceuticals, Ambrx Inc., Akros Pharma, Vascular Biogenics, Theradiag, Forward Pharma, Regeneron, Galapagos, Seres Health, Ritter Pharmaceuticals, Theravance, Palatin, Biogen, and the University of Western Ontario (owner of Robarts Clinical Trials); non-financial support from Receptos